1989
DOI: 10.1002/mds.870040301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of etybenzatropine and diazepam on levodopa‐induced diphasic dyskinesias in Parkinson's disease

Abstract: Levodopa-induced onset and end-of-dose dyskinesia are rare but disabling disorders. Although they can be attenuated by increasing and dividing the daily dose of levodopa, this does not constitute a therapeutic approach. In this pilot study, etybenzatropine, an anticholinergic drug, and diazepam, a selective benzodiazepine, were administered in addition to a single dose of levodopa in nine patients with Parkinson's disease. Both drugs tended to decrease the severity and the duration of onset and end-of-dose dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Additionally, the anti-muscarinic compound, dicyclomine, alleviates severity of dyskinesia in chronic L-DOPA treated Pitx3 ak/ak mice and in 6-OHDA lesioned mice (Ding et al, 2011). In a small cohort of humans, co-administration of L-DOPA with the anticholinergic etybenzatropine decreased the severity of end-of-dose dyskinesia, and also increased the duration of action of L-DOPA (Pourcher et al, 1989) although older studies have noted worsening of LID by anticholinergics (Birket-Smith, 1974). Collectively, these conflicting results may indicate different contributions between pharmacological anticholinergic manipulations that target many cell types versus cell type-specific modulation of ChI to the expression of LID.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the anti-muscarinic compound, dicyclomine, alleviates severity of dyskinesia in chronic L-DOPA treated Pitx3 ak/ak mice and in 6-OHDA lesioned mice (Ding et al, 2011). In a small cohort of humans, co-administration of L-DOPA with the anticholinergic etybenzatropine decreased the severity of end-of-dose dyskinesia, and also increased the duration of action of L-DOPA (Pourcher et al, 1989) although older studies have noted worsening of LID by anticholinergics (Birket-Smith, 1974). Collectively, these conflicting results may indicate different contributions between pharmacological anticholinergic manipulations that target many cell types versus cell type-specific modulation of ChI to the expression of LID.…”
Section: Discussionmentioning
confidence: 96%
“…In the MPTP-lesioned NHP, the positive GABA A allosteric modulator diazepam alleviated LID without impairing L-DOPA antiparkinsonian action (Gomez-Mancilla and Bedard, 1993), whereas the GABA B agonist baclofen did not alter LID severity, but reduced L-DOPA antiparkinsonian efficacy (Gomez-Mancilla and Bedard, 1993). Diazepam also exerted a mild antidyskinetic effect in a pilot clinical study (Pourcher et al, 1989). In a case report, zolpidem, a GABA Apositive allosteric modulator (Smith et al, 2001), significantly alleviated LID (Ruzicka et al, 2000), although antidyskinetic effects of zolpidem were not reported in another clinical study (Daniele et al, 1997).…”
Section: The Gabaergic Systemmentioning
confidence: 98%
“…In the case of benzodiazepines, diazepam reduced LID in MPTP primates (Gomez-Mancilla and Bedard, 1993) and in a pilot study in PD patients (Pourcher et al, 1989). Positive modulators of the GABA A receptor, such as zolpidem and topiramate, show conflicting results.…”
Section: The Gabaergic Systemmentioning
confidence: 97%